Analytical and diagnostic accuracy of "second generation" assays for thyrotrophin receptor antibodies with radioactive and chemiluminescent tracers. Issue 4 (26th March 2004) - Villalta, D; Orunesu, E; Tozzoli, R; Montagna, P; Pesce, G; Bizzaro, N; Bagnasco, M
Abstract : Aims: To investigate the analytical and diagnostic accuracy of thyrotrophin (TSH) receptor antibody assays using recombinant human TSH receptors. Methods: Sera from 68 patients with Graves' disease, 23 patients with autoimmune thyroiditis, and 119 healthy controls were evaluated in four different laboratories using both radioactive and chemiluminescent tracers. Functional sensitivity, interlaboratory precision, optimal cutoff values for Graves' disease, and the correlation between the two methods were evaluated. Results: Functional sensitivity was 0.98 IU/litre for both assays. Interlaboratory precision, expressed as per cent coefficient of variation over a wide range of antibody concentrations, varied from 5.7% to 15.1% for the radioligand, and from 6.6% to 19.9% for the chemiluminescence assay. The two methods (radioactive and chemiluminescent) were closely correlated. All the sera from untreated or relapsing patients with Graves' disease gave TSH receptor antibody values above 2.1 IU/litre, whereas in none of the healthy controls did values exceed 2.5 IU/litre. Receiver operating curve analysis allowed an optimal cutoff point to be defined at 1.99 IU/litre, according to a sensitivity of 100% and specificity of 99.1%. Conclusions: These data show the high analytical and diagnostic accuracy of the human TSH receptor assays, both with radioactive and chemiluminescent tracers, when both functional sensitivity and interlaboratory reproducibility are considered. These two methods could be proposed as first line diagnostic markers for Graves' disease.